Root and tuber crop programs at the University of the West Indies - Ferguson, T.U.; Wilson, L.A (International Center for Tropical Agriculture, 1986)
Research work on root crops (yam, sweet potato, cassava, potato, and aroids, in particular, cocoyam), carried out by the Faculty of Agriculture of the U. of West Indies, is summarized. Regarding cassava, the major achievements have been the identification of factors limiting its development in the region, the understanding of its growth mechanisms, selection, development, and release of cv., development of improved systems for mechanization, quantification of yield performance on different soil types, studies on the dormancy mechanism in root crops, and development of packages of cultural practices. Outreach and training activities are mentioned, and proposals for research activities on root crops are given. (CIAT)